Analisis Pengaruh Sistem Double Order dan Mode Hemat terhadap Kepuasan Pelanggan Gojek di Kota Ungaran - Fajar Suryatama; Pitaloka Dharma Ayu; Yunita Khusnul Khotimah (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Limited fiscal space and the demand for increased profits prompted PT. GoTo Gojek Tokopedia Indonesia Tbk to reduce reliance on discount programs that were proven to reduce company profits. As an alternative, in early 2023 GoJek launched two service innovations, namely the double order system and the economy mode feature, with the aim of maintaining consumer interest and satisfaction amidst increasingly fierce competition. This study aims to analyze the effect of the double order system and the economy mode feature on GoJek consumer satisfaction. The research method used is descriptive quantitative with analysis techniques in the form of validity tests, reliability, multiple linear regression, determination tests, t-tests, and F-tests. Data processing was carried out using the SPSS version 25 application. The results showed that the double order system variable had a positive and significant effect on consumer satisfaction with a regression coefficient value of 0.295 and a calculated t-value of 3.294 greater than the t-table of 1.985 and a significance level of 0.001. The economy mode variable also shows a positive and significant influence on consumer satisfaction with a regression coefficient value of 0.493 and a calculated t value of 6.118 with a significance of 0.000. The adjusted R square value of 0.422 indicates that the two independent variables are able to explain 42.2% of the variation in consumer satisfaction. The F test produces a value of 37.195 which is greater than the F table of 3.09, so that all research hypotheses are declared accepted.